Crackers from Fresh Water Snail (Pila ampullacea) Waste as Alternative Nutritious Food. Issue 1 (March 2020) - Broto, R T D W; Arifan, F; Setyati, W A; Eldiarosa, K; Zein, A R
Abstract: Fresh water snail ( Pila ampullacea) is large fresh water snail that can be found in rice fields, ponds, lakes and marshes. Most of them live in paddy fields and become pests for its plant thus the farmer tries to eradicate. Whereas, aquatic animals especially snail contain high level of protein with an amino acid profile similar with the meat land animals, thus making it beneficial to health in countries where snail exists. Thus, fresh water snail can be used as a raw material in producing foods or snacks, one of the famous snack in Southeast Asian countries is cracker. Pila ampullacea was obtained from the swamp and was cleaned it up by removed the flesh from its shell and used the water then production of the crackers. Nutrition contents of the fresh water snail cracker is protein (10.67%) and lipid (0.06%). The organoleptic analysis of crispiness was shown good result with mean score is 4.1.